The Protective Effect of the Ethanol Leaf Extract of Andrographis Paniculata on Cisplatin-Induced Acute Kidney Injury in Rats Through nrf2/KIM-1 Signalling Pathway - Adeoye, Bisi Olajumoke; Asenuga, Ebunoluwa Racheal; Oyagbemi, Ademola Adetokunbo; Omobowale, Temidayo Olutayo; Adedapo, Adeolu A (Drug Research, 2018)
The ethanol leaf extract of Andrographis paniculata was used to ameliorate the renal toxicity induced by cisplatin in 28 rats divided into four groups of seven rats per group. Group A received normal saline for the duration of the experiment. Group B animals were treated with cisplatin (10 mg/kg i.p) on day 1 and 3 days after received normal saline for the next 7 days while groups C and D animals also received 10 mg/kg dose of cisplatin on day 1 but after 3 days were then respectively treated with 200 and 400 mg/kg doses of the extract of Andrographis paniculata for the remaining 7 days through oral administration. Serum chemistry was used for the determination of markers of oxidative stress, anti-oxidant enzymes, serum biomarkers etc. Histopathology and immunohistochemistry were also carried out. Results showed that all oxidative stress markers assayed were significantly increased in group B animals but reverse is the case for groups C and D. On the other hand, antioxidant enzymes assayed experienced significant increase for groups C and D while these parameters experienced significant decrease for group B animals. Histopathology showed severe infiltration of inflammatory cells into renal tissues of group B animals whereas for groups C and D animals, only moderate glomerular degeneration was noted. In immunohistochemistry, while there is higher expression of KIM-1 for group B, there was a lower expression in groups C and D. Again, there was lower expression of Nrf2 for group B but higher expressions in groups C and D animals.
Keywords: Andrographis paniculata; cisplatin; nrf2; KIM-1; anti-oxidant